Hydration monitoring and rehydration guidance system for athletes based on urine color’s L*a*b* parameters - Feng, Yiwei; Fang, Guoliang; Li, Minghai; Cui, Shuqiang; Geng, Xue; Qu, Chaoyi; Zhao, Jiexiu (Frontiers in Bioengineering and Biotechnology, 2022)
Maintaining proper hydration is essential for athletes to sustain optimal performance and preserve their physical health. Existing studies have confirmed that urine color is one of the effective indicators for the subjective evaluation of athletes’ hydration through the urine color chart. In recent years, the L*a*b* color model has been widely used in the objective quantitative analysis of color. The L* value represents the luminance change from black to white, the a* value represents the chromaticity change from green to red, and the b* value represents the chromaticity change from blue to yellow. The research team developed a urine hydration monitoring and rehydration guidance system based on the urine color’s L*a*b* parameters via wireless network technology and digital image technology. The hardware structure of the system is composed of a cuvette, a standard light source, a camera, an image collector, a host system, and a touch screen system. The software system is composed of user information, image acquisition, image processing, and image recognition. The system exhibits stable performance, a friendly operation interface, and simple and fast testing. It can objectively and accurately evaluate the hydration of athletes and provide personalized rehydration guidance. The system offers a new method for solving practical problems in sports training, and it has broad application prospects.